The influence of temperature on the apparent lipid digestibility in Atlantic salmon (Salmo salar) fed Calanus finmarchicus oil at two dietary levels - Bogevik, Andre S; Henderson, R James; Mundheim, Harald; Waagbo, Rune; Tocher, Douglas R; Olsen, Rolf E (Aquaculture, 2010)
Oils extracted from the marine zooplankton, Calanus finmarchicus, have high levels of n-3 highly unsaturated fatty acids (HUFA) and are therefore of interest as an alternative lipid source in aquafeeds. Copepod lipid is composed mainly of wax esters (WE) with high levels of saturated fatty acids and monounsaturated fatty alcohols which are considered hard to digest, especially at low temperatures. This assumption has however not been verified and for this reason the present study examined the digestibility of diets containing high levels of WE and two fat levels in Atlantic salmon reared at 3 and 12 °C. The fish were acclimated for one month to 3 °C (485 g) and 12 °C (599 g) and then fed one of four diets, high fat fish oil (33% lipid, HFFO), high fat Calanus oil (32% lipid, HFCO), low fat fish oil (17% lipid, LFFO) and low fat Calanus oil (19% lipid, LFCO). The fish meal lipid content was lowered by the use of lipid-extracted fish oil (2.3% lipid). This enabled a level of 50% WE in the LFCO and HFCO oils, compared to 0% in the LFFO and HFFO diets. The fish were then allowed to grow to around 100% of initial weight (220 days at 3 °C and 67 days at 12 °C) and then analysed for faecal lipid digestibility, bile volume, bile composition and intestinal lipolytic activity. Differences were observed in all these parameters in relation to temperature, type of dietary oil and the lipid level in the diet. Faecal lipid content and lipid class composition were dependent on rearing temperature and the type of dietary lipid. Highest levels of undigested lipids were observed in the faeces of fish fed CO. Wax ester-derived fatty alcohols, particularly 20:1n-9 and 22:1n-11, were less extensively digested than corresponding fatty acids from FO at both fat levels and temperatures. Fish kept at 12 ºC had a significantly higher bile volume than fish at 3 ºC and higher volumes were found in fish fed CO diets compared to FO. Decreased faecal passage time at lower temperatures, was not sufficient to ensure high digestibility since the ...